Education for food sovereignty as transformative ethical practice. Issue 7 (October 2019) - Mann, Alana
The Anthropocene is a site of domination and resistance for those opposed to the corporatised food regime. The peasant farmers' movement, La Vía Campesina, uses pedagogical techniques based on Freirian horizontal communication methodology to contest the structural and ideological elements of this regime. This article analyses these techniques, which include farmer-to-farmer learning ( campesino-a-campesino ) and dialogue among different knowledges and ways of knowing ( diàlogo de saberes ). Drawing on case studies of Brazil and Chile, the author analyses how peasant farmer organisations engage in horizontal exchange and learning processes to collectively build a shared vision of agroecology, present alternative framings of food scarcity, and challenge the modes of power that operate in the arena of food politics. She explores how movement members apply social process methodology to link the food sovereignty framework with indigenous knowledge, gender equity and post-colonial theory and in doing so demonstrates how these participatory processes generate critical consciousness of the social and environmental unsustainability of the global food system. This mobilises peasant farmers to contest the power structures that shape their food environments, and also to focus on social and economic justice within their communities.